Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae) - Ferrari, Augusto; Schwertner, Cristiano Feldens; Grazia, Jocelia (Zootaxa, 2010)
In this paper, the genus Nezara Amyot & Serville is reviewed and a hypothesis of relationships among its species is proposed. Also, diagnoses for the genus and the 12 included species are provided. A key to separate the species is also provided. Of the seven other species assigned to Nezara in the literature, four of them are considered incertae sedis, two are transferred to different genera, and one is considered a junior synonym. The cladistic analysis include 15 taxa and 34 characters. The cladogram was rooted with Carpocoris purpureipennis (DeGeer); outgroup comparison also include species of the sister-groups Aethemenes chloris (Dallas), and Pseudoacrosternum cachani Day. The results showed Nezara as a monophyletic taxon. Biogeographical scenarios of the evolution of Nezara were discussed.